2008
DOI: 10.1136/bjsm.2008.049403
|View full text |Cite
|
Sign up to set email alerts
|

Ten year follow-up study comparing conservative versus operative treatment of anterior cruciate ligament ruptures. A matched-pair analysis of high level athletes

Abstract: We conclude that the instability repair using a bone-patella-tendon-bone anterior cruciate ligament reconstruction is a good knee stabilising operation. Both treatment options however show similar patient outcome at 10 year follow up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
175
1
10

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(195 citation statements)
references
References 35 publications
9
175
1
10
Order By: Relevance
“…Similarly, a prospective cohort study by Moknes et al found no difference in performance-based outcomes and the number of subjects returning to pre-injury activity levels between non-operatively and operatively treated groups 67 . In a case-control study Meuffels et al also found no statistical difference in activity levels or subjective and objective functional outcomes at 10 years post-injury between patients treated conservatively or operatively 68 .…”
Section: Surgical Vs Non-surgical Treatmentmentioning
confidence: 99%
“…Similarly, a prospective cohort study by Moknes et al found no difference in performance-based outcomes and the number of subjects returning to pre-injury activity levels between non-operatively and operatively treated groups 67 . In a case-control study Meuffels et al also found no statistical difference in activity levels or subjective and objective functional outcomes at 10 years post-injury between patients treated conservatively or operatively 68 .…”
Section: Surgical Vs Non-surgical Treatmentmentioning
confidence: 99%
“…The rate of osteoarthritis changes is higher in patients with reconstructed ACLs compared with patients with chronic ACL deficiency who had not undergone ACL reconstruction. Meuffels et al 19 compared 25 patients with ACL deficiency who received only conservative management for 10 years with a matched group of patients who received bone-patella tendon-bone ACL reconstruction 10 years previously and found more radiographic evidence of osteoarthritis changes in the surgical group (28% vs 48%, respectively), although the operated knees were more stable.…”
Section: Prevention Of Osteoarthritismentioning
confidence: 99%
“…Since ACL injuries contribute to an increased risk of knee osteoarthritis [14,15], the current gold standard for the management of complete ACL rupture is reconstruction using a tendon autograft. However, there are no highquality randomized controlled trials comparing ACL reconstruction with other modalities of treatment [16][17][18][19].…”
Section: Current Treatment For Acl Injuriesmentioning
confidence: 99%
“…Since ACL injuries contribute to an increased risk of knee osteoarthritis [14,15], the current gold standard for the management of complete ACL rupture is reconstruction using a tendon autograft. However, there are no highquality randomized controlled trials comparing ACL reconstruction with other modalities of treatment [16][17][18][19].However, it is clear that the spontaneous healing capacity of the ACL has been underestimated. Several clinical studies have reported results of ACL healing with non-surgical treatment alone [20][21][22].…”
mentioning
confidence: 99%